Effect of the Triaxiality in Plane Stress Conditions. Triaxiality Effect in a PVC Material - Selini, N.; Elmeguenni, M.; Benguediab, M. (Engineering, Technology & Applied Science Research, 2013)
Polymer materials are gaining more and more importance in engineering applications. A new methodology of analysis is required in order to assess the capability of such material in withstanding complex loads. Therefore, the behavior of these materials currently arouses a great research interest. The use of PVC plastic pipes in pressure vessels and pipelines has increased rapidly in the last decade. In order to determine the plastic behavior of PVC, an experimental method is presented. Through the results obtained from experimental tests, in the first part of this paper, we investigate the use of a phenomenological model proposed by G’Sell and Jonas. The true stress-strain response under large plastic deformation was investigated in different stress triaxiality frameworks. Particular attention was given to volumetric strain evolution, separation resulting from elastic volumetric strain, plastic volumetric strain and pure shear. The effect of stress triaxiality on plastic instability and fracture strain was also examined. The deformation process should be considered as explained, and the anisotropic plastic response induced by the deformation could be introduced in constitutive equations of G’Sell.